2021
DOI: 10.3390/ijerph18158119
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Social Media Use and Their Voluntary Garbage Sorting Intention: A Sequential Mediation Model

Abstract: Encouraging adolescents to sort garbage is vital for the sustainable development of the ecological environment. This study investigates the relationship between adolescents’ social media use and their garbage sorting intention. A survey, in both online and paper-based versions, was distributed in 2020 in Shanghai and a total number of 605 valid responses were obtained. This study supports the proposed sequential mediation model, indicating that adolescents’ social media use increased their garbage sorting inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…What can be seen in the knowledge test of university students on waste classification is that the knowledge of university students on waste classification is not satisfactory, and the knowledge education needs to be strengthened. The results of the research show that nearly half of the students do not yet know the standards of the four categories of waste classification: food waste, recyclable waste, hazardous waste, and other waste, and the average score of 1,282 college students on the knowledge of waste classification is only 5.56 (out of 10), which is consistent with the findings of the study of Ai et al (43). In addition, we found that first-year university students performed significantly better than other years in terms of their knowledge of waste classification.…”
Section: Discussionsupporting
confidence: 88%
“…What can be seen in the knowledge test of university students on waste classification is that the knowledge of university students on waste classification is not satisfactory, and the knowledge education needs to be strengthened. The results of the research show that nearly half of the students do not yet know the standards of the four categories of waste classification: food waste, recyclable waste, hazardous waste, and other waste, and the average score of 1,282 college students on the knowledge of waste classification is only 5.56 (out of 10), which is consistent with the findings of the study of Ai et al (43). In addition, we found that first-year university students performed significantly better than other years in terms of their knowledge of waste classification.…”
Section: Discussionsupporting
confidence: 88%
“…The PROCESS macro is particularly adept at accounting for multiple mediation effects operating in parallel, enabling users to formally assess sequential indirect links while combining mediation and moderation tests (Hayes, 2015; Hayes et al, 2017). Following prior research (Ai et al, 2021; Zhuang et al, 2018), we computed regression equations and estimated the mediator variable models using sleep variables and self-control as the respective sequential mediators, enabling us to estimate indirect effects by bootstrapping methods (1000 bootstraps). The results of these analyses are shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Both cognitive and affective aspects of social media affect tourist' pro-environmental behavior (Sultan et al, 2021). Social media is also found to have influence on individuals' pro-environmental behavior through communicative role that social media has (Ai et al, 2021). Through shared information on social media, travel opinion leader also influence tourists' behavior (Javed et al, 2020;Vrana & Zafiropoulos, 2010;Yoo et al, 2011).…”
Section: Relationship Between Social Media Ugc and Pro-environmental ...mentioning
confidence: 99%